Chapter 6 The influence of politics on girls' education in Ethiopia - Yorke, Louise (Taylor & Francis, 2021)
In this chapter we consider why education systems have not yet achieved equitable access and learning for all girls, despite high-level government commitment. Taking Ethiopia as a case study, we refer to the 'domains of power' framework (Hickey & Hossain, 2019) to explore the influence of politics on progress in girls' education, focusing on the interaction between the political settlement and the education policy domain. The analysis draws on data from the Research on Improving Systems of Education (RISE) Ethiopia programme, including analysis of government documents, actor mapping and interviews with 150 key government stakeholders across seven regions and city administrations in Ethiopia. Adopting a gender lens, we take account of the influence and interaction of informal institutions within the education domain. We find that the education system cannot be considered to be a gender-neutral site given that women continue to be absent from positions of power. In addition, stakeholders' ideas about the nature of gender roles influence their attitudes, behaviour and actions, holding back progress towards the high-level commitments.